Motor Car Advertisements Texts: An Analysis of Pragmatic - Herlina, Herlina (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
In this paper the writer tries to analyze the motor vehicle advertisement texts from pragmatics point of view through classifying and describing the speech act types. Since this research is a qualitative, the writer uses descriptive method with speech act theory of pragmatics from Cutting and Yule. The writer collects the data from www.adsoftheworld.com, www.adslogans.co.uk and www.textart.ru, March 18th 2014. In analyzing data, the writer classified the data into table list. The classification is divided into speech act types and speech act levels, they are locutionary act as the ad texts and illocutionary act as the advertisers intention behind.  At the end of the research is found that related to the purpose of the ad in conveying its audience, there are representative and directive of speech act types. Representative are those kinds of speech act that state what the speaker believes to be the case or not and directive those kinds of speech acts that the speakers use to get someone else to do something. Therefore, the research hopefully brings about more comprehension on the motor vehicle advertisements which are often found in motor vehicle advertisements texts.